2019
DOI: 10.1186/s12302-019-0262-5
|View full text |Cite
|
Sign up to set email alerts
|

Moss species-specific accumulation of atmospheric deposition?

Abstract: Background: This article presents statistical analyses of elements concentrations in mosses collected in two monitoring programmes: 1. The German moss monitoring as part of the European Moss Survey conducted in 1990, 1995, 2000, 2005 and 2015 at 592, 1026, 1028, 726 and 400 sites across Germany, respectively, and chemically analysed according to harmonised methods throughout Europe; and 2. The moss surveys additionally performed throughout Bavaria, federal state of Germany. The evaluations of the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In 2005, a pilot study of nitrogen, persistent organic pollutants (POPs), polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) concentrations in mosses was carried out in selected countries using the pleurocarpous species since these species spread a thick cushion mats which has high surface-to-volume ratio that favour high accumulation of pollutants (Harmens et al, 2013). Schröder & Nickel, (2019) found that 74 % of the moss biomonitoring studies employes Pleurozium schreberi, Hypnum cupressiforme, Hylocomium splendens and Psedoscleropodium purum as biomonitors in Europe and North America. Pleurozium schreberi was able to accumulate PAHs and PCBs road traffic (Sucharová & Holá, 2014a) (Danielson et al, 2016).…”
Section: Moss Distribution and Its Ability To Absorb Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, a pilot study of nitrogen, persistent organic pollutants (POPs), polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) concentrations in mosses was carried out in selected countries using the pleurocarpous species since these species spread a thick cushion mats which has high surface-to-volume ratio that favour high accumulation of pollutants (Harmens et al, 2013). Schröder & Nickel, (2019) found that 74 % of the moss biomonitoring studies employes Pleurozium schreberi, Hypnum cupressiforme, Hylocomium splendens and Psedoscleropodium purum as biomonitors in Europe and North America. Pleurozium schreberi was able to accumulate PAHs and PCBs road traffic (Sucharová & Holá, 2014a) (Danielson et al, 2016).…”
Section: Moss Distribution and Its Ability To Absorb Pollutantsmentioning
confidence: 99%
“…Wu et al, 2014), garages (G. Vuković et al, 2013), airports (Turgut et al, 2019), petroleum refinery (Cortis et al, 2016) and bodies of water (Gecheva et al, 2020), moss bags method assists the monitoring of air around volcanoes (Calabrese et al, 2015) and in cold climate regions (Salo et al, 2016). Airborne pollutants accumulated in mosses through wet or dry deposition remain for at least 2 to 3 years and reflect the level of pollution (Fabure et al, 2010;Schröder & Nickel, 2019). Details on studies that used both types of monitoring are shown in Table 1 and Table 1.1.…”
Section: Type Of Moss Monitoringmentioning
confidence: 99%
“…Moreover, the predominant moss species within the Czech survey were Pleurozium schreberi and Scleropodium purum, while the Spanish and Turkish studies were based on the collection of Hypnum cupressiforme (Hedw.). Though it is supposed that elements concentrations in moss tissue are species-dependent [56,91,92], the information on the interspecies calibration for concerned moss species is still lacking; thus, it could not be performed. The comparison presented in Table 2 shows that levels of all elements recorded in Třinec were significantly higher in both June and October than in the Czech state-wide data, with the exception of Mn.…”
Section: Elements Contentmentioning
confidence: 99%
“…It is used to distinguish and prioritize accumulation pathways of a given metal (Tan et al, 2000) and to determine the degree and type of contamination, mainly in industrial areas (De Agostini et al, 2020; Morales‐Casa et al, 2019). Nowadays, it is rarely applied, knowing that the pollutants accumulated by mosses are the sum of both dry and wet deposition (Schröder & Nickel, 2019; Xiao & Liu, 2011).…”
Section: Introductionmentioning
confidence: 99%